Gradasi Pembiasaan Ibadah Anak dalam Keluarga (Analisis Teks Hadis dan Implikasinya terhadap Pedagogi PAI Usia Dini) - Risnawati Hannang; Jusmaliah J; Andi Satrianingsih; Nur Azizah; Syahidah Asia Almuqarramah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to formulate a pedagogical model of Islamic Religious Education (IRE) for early childhood within the family through the application of the gradation principle (at-tadarruj) based on the analysis of Hadith texts. This study employs a qualitative approach using the library research method. Data collection instruments center on documentation studies of primary sources in the form of Hadith texts (specifically narrated by Abu Dawud), as well as secondary sources consisting of scientific literature and reputable journals. Data analysis techniques include content analysis, semantic and linguistic analysis of the matn, historical context examination (asbabul wurud), hermeneutic methods for contextualization, and a descriptive-analytical approach. The findings emphasize that habituating children to worship must be conducted continuously and gradually according to their psychological and cognitive development phases. Worship education for ages 0–7 is most effective using habituation (ta'wid), exemplary role-modeling (uswah hasanah), and concrete experiences without the burden of religious obligations. Linguistic analysis of the diction muru marks a transition toward active, rational, persuasive, and gentle (rifq) instruction during the tamyiz period (ages 7–10). For ages 10 and above, the diction wadhribu is redefined as a form of educative firmness ('uqubah tarbawiyyah) based on logical consequences, accompanied by the instruction to separate sleeping quarters (wa farriqu) as a means of privacy education, gender awareness, and independence.